POLA INTERAKSI PENGGEMAR DENGAN IDOLA (Studi Kasus Band Reggae Lhaiyo Semarang) - akbar, zulkarnaen (Jurnal Seni Musik, 2014)
Lhaiyo is one of actor that present Semarang reggae face and can extensively attract attention. In other word, Lhaiyo is easily accepted in society. Existence of Lhaiyo band is also supportedby fans who always give support in each performance. Lhaiyo Positions which are unique and different from other reggae band get attention this research. Although it is against the flow, this band can attract attention all of people who do not love reggae music. This research has a goal to discover factors that affect society acceptance regarding Lhaiyo band and patterns of interaction happening among fans with reggae Lhaiyo band. Used in this research, Method is qualitative approach. it is Data collection techniques with observation, interview and documentation. Researches indicate that there are factors which influence getting fans against Lhaiyo band are internal factor and externals factors. Moreover, there is a relation happening between Lhaiyo band with their fans. Essentially, it is relation between fans with artist. As artist, connection which happend among Lhaiyo Band with their fans still as restricted sympathy and empathy. Imitation process or identification of fans with their artist has happened in this social interaction.